Analyzing Seventh Grader’s English Speaking Materials Using Microlearning and Critical Thinking Frameworks - Pamadeng Lette, Af Yiyin; Iskandar, Ifan; Suseno, Muchlas (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
Microlearning and critical thinking are essential for effective English speaking, yet their integration in existing materials for seventh graders remains inadequate. As a result, this study aimed to develop microlearning- based English speaking materials enriched with critical thinking for seventh graders. Using content analysis, this study analyzed these materials through modified frameworks of microlearning and critical thinking (Allela, 2021; Leong et al., 2021; De Gagne, 2019; Hug, 2005; Anderson & Krathwohl, 2001). English teachers were also interviewed to confirm material usage and assess the integration of microlearning and critical thinking. Content analysis of one national textbooks (Kurikulum Merdeka) and two teacher- created materials, alongside interviews with three teachers, revealed deficiencies in material design conciseness (LM_ML02), curriculum alignment (LM_ML05), and microlearning object incorporation (LM_ML06). Moreover, coverage of critical thinking skills such as analysis (CT4), evaluation (CT5), synthesis (CT6) was also limited. These findings highlighted the need for developing microlearning-based English speaking materials enriched with critical thinking for seventh graders. However, the focus on this grade level limits generalizability of the results. Therefore, further research across different academic levels and education context is recommended.